Transcriptome profiling for precision cancer medicine using shallow nanopore cDNA sequencing - Mock, Andreas; Braun, Melissa; Scholl, Claudia; Fröhling, Stefan; Erkut, Cihan (Scientific reports, 2023)
Transcriptome profiling is a mainstay of translational cancer research and is increasingly finding its way into precision oncology. While bulk RNA sequencing (RNA-seq) is widely available, high investment costs and long data return time are limiting factors for clinical applications. We investigated a portable nanopore long-read sequencing device (MinION, Oxford Nanopore Technologies) for transcriptome profiling of tumors. In particular, we investigated the impact of lower coverage than that of larger sequencing devices by comparing shallow nanopore RNA-seq data with short-read RNA-seq data generated using reversible dye terminator technology (Illumina) for ten samples representing four cancer types. ...